Identification and Orientation on Spatial Arrangement of Wajo Traditional Village, Keo Tengah, Nagekeo Regency - Lake, Reginaldo Christophori; Purbadi, Yohanes Djarot; Harmans, Herman Florianus (University of Merdeka Malang, 2020)
The purpose of this paper is to describe the uniqueness of spatial arrangement of Wajo traditional villages in Nagekeo district, which is designed based on local wisdom. Traditional settlements in Indonesia have a spatial concept that has the potential to become the basis of contemporary architecture. The spatial arrangement of traditional settlements of Wajo village is interesting to disclose the principle and its constituent elements as one of Indonesia's architectural properties that maintaining local culture. The problem under study is the dominant (important) aspects underlying the spatial concept of traditional village settlements Wajo custom. The method used is to study literature in various writings on the spatial layout phenomenon of traditional settlements, as well as the elaboration of physical theories (structuring principles) and non-physical theories (identification and orientation) to find the dominant relationships that form the spatial layout of the Wajo traditional village. The analysis is based on Schulz's phenomenological paradigm and Salura's design principle theory. From the results of the analysis, it was found that the spatial concept of the Wajo traditional village is a relation of the perception of the surrounding environment, site, shape, figure and natural-cultural cycle influenced by dominant factors namely the top-down orientation (sacred and profane) and physical adaptation of the topography of the place, as well as elements binding (datum) in the form of tribal order (the existence of mosalaki), cultural symbols (customs), and spiritual (ancestors).Â DOI:Â https://doi.org/10.26905/lw.v12i1.3581 Â